7TH MALAYSIA PLAN : RESEARCH ABSTRACTS - Universiti Teknologi Malaysia. Research Management Centre 3591 (Skudai : Universiti Teknologi Malaysia, 2007)
The first edition of Research Abstracts (The Seventh Malaysia Plan (RMK7)) is published to fulfill the needs of the university and the Malaysian public inline with the university's aspiration to achieve world class status. The Research Management Centre (RMC) has been entrusted to compile the final research reports and abstracts for the benefit of the public to enhance the research findings in the field of Science and Technology. Under the Seventh Malaysia Plan (RM7), RMC has managed 1131 projects in various research categories of which some have been selected for this publication. This publication, apart from promoting the research findings would also benefit all parties concerned in particular industries. The sharing of knowledge would enable the university to produce researchers who are not only capable but also competitive in the field of science and technology. This is important for the university in order to compete among institutions of higher learning at a global level. It is intended that this publication would be a source of reference for future research.